Fatty acid composition of the methylotrophic yeast Komagataella phaffii grown under low‐ and high‐methanol conditions. Issue 10 (15th June 2021) - Ma, Pengli; Takashima, Shigeo; Fujita, Chikako; Yamada, Saya; Oshima, Yusuke; Cai, Hao‐Liang; Yurimoto, Hiroya; Sakai, Yasuyoshi; Hayakawa, Takashi; Shimada, Masaya; Ning, Xia; Wei, Baoyao; et al.
Abstract: In this study, we analysed the intracellular fatty acid profiles of Komagataella phaffii during methylotrophic growth. K. phaffii grown on methanol had significantly lower total fatty acid contents in the cells compared with glucose‐grown cells. C18 and C16 fatty acids were the predominant fatty acids in K. phaffii, although the contents of odd‐chain fatty acids such as C17 fatty acids were also relatively high. Moreover, the intracellular fatty acid composition of K. phaffii changed in response to not only carbon sources but also methanol concentrations: C17 fatty acids and C18:2 content increased significantly as methanol concentration increased, whereas C18:1 and C18:3 contents were significantly lower in methanol‐grown cells. The intracellular content of unidentified compounds (Cn H2n O4 ), on the other hand, was significantly greater in cells grown on methanol. As the intracellular contents of these Cn H2n O4 compounds were significantly higher in a gene‐disrupted strain for glutathione peroxidase ( gpx1 Δ) than in the wild‐type strain, we presume that the Cn H2n O4 compounds are fatty acid peroxides. These results indicate that K. phaffii can coordinate intracellular fatty acid composition during methylotrophic growth in order to adapt to high‐methanol conditions and that certain fatty acid species such as C17:0, C17:1, C17:2 and C18:2 may be related to the physiological functions by which K. phaffii adapts to high‐methanol conditions.